Safety and efficacy of Bacillus subtilis PB6 (Bacillus subtilis ATCC PTA‐6737) as a feed additive for sows - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Guido Rychen; Gabriele Aquilina; Giovanna Azimonti; Vasileios Bampidis; Maria De Lourdes Bastos; Georges Bories; Andrew Chesson; Pier Sandro Cocconcelli; Gerhard Flachowsky; Jürgen Gropp; Boris Kolar; et al. (EFSA Journal, 2017)
Abstract Bacillus subtilis PB6 is a feed additive based on viable spores of a strain of Bacillus subtilis. EFSA has already issued several opinions on the safety and efficacy of the additive when used in the feed for a number of avian and porcine species/categories. The applicant is now seeking authorisation for use in sows in order to have benefits in piglets. In the course of previous assessments, no evidence of a toxigenic potential or resistance to relevant antibiotics was found. Consequently, the strain of B. subtilis in the additive, following the qualified presumption of safety approach to safety assessment, is presumed safe for target animals including sows and their offspring, consumers and the environment. In a previous assessment, it was also concluded that the additive is not a skin/eye irritant or a skin sensitiser and that there were no concerns on respiratory sensitisation. The use of the additive with feed for sows is considered unlikely to introduce hazards for users of the product not already considered. Five studies are described in which groups of sows given the additive for a minimum period from the last 3 weeks of pregnancy, throughout farrowing and lactation, until weaning of piglets were compared with a control group. In only two of five studies, there was a significant beneficial effect seen in terms of piglet performance. However, when data from the four similar were pooled and analysed, significant increases in weaned weight and average daily gain were indicated for piglets from sows given the additive. Consequently, the FEEDAP Panel concludes that Bacillus subtilis PB6 when added to diets of sows from 3 weeks before parturition until weaning of piglets at a dose of 1 × 108 CFU/kg complete feed has the potential to improve the growth of piglets from birth to weaning.